Delayed Aspiration of Air Emboli from the Central Venous Catheter in a Case of Suspected Massive Venous Air Embolism: A Therapeutic Success - Khandelwal, Ankur; Nayak, Sudhansu S.; Bhatia, Anshil; Shrivastava, Amit K.; Bhardwaj, Vikas (Journal of Neuroanaesthesiology and Critical Care, 2022)
Venous air embolism (VAE), though, clinically benign in majority of cases, the significant ones can lead to life-threatening cardiopulmonary and neurological consequences. Though studies mention the success rate of only 6 to 16% in aspirating air from the central venous catheter (CVC) during VAE, the technique is very specific for diagnosing VAE and has high therapeutic significance. We report a case in which delayed aspiration of air emboli from the CVC in suspected massive VAE during decompressive craniectomy resulted in rapid resolution of hemodynamic instability. If not inserted previously, CVC may be considered in a hemodynamically unstable patient with suspected VAE.
Keywords: air embolism; central venous catheters; hemodynamic; neurosurgery